Multivariate Analysis of SERS Signals for Multianalyte Detection in Co3O4-Ag Substrates - Tieppo, Kamila; Fonsaca, Jéssica E.S.; Martins, Kevin S.B.; Teixeira, Wanderson S.R. [UNESP]; de Matos, Christiano J.S. (Optica Publishing Group, 2023)
We propose a new SERS substrate based on a Co3O4-Ag nanocomposite and employ it to detect two different chemical species. Multivariate analysis is then used to individually identify the presence of each species.